A Numerical Study on the Effect of Temperature and Composition on the Flammability of Methane–Hydrogen Sulfide Mixtures. Issue 9 (2nd September 2019) - Pio, G.; Barba, D.; Palma, V.; Salzano, E.
ABSTRACT: The growing demand of natural gas inspires existing and new projects in topographical areas where the hydrocarbon extraction meets severe safety challenges due to the presence of hydrogen sulfide (H2 S) in natural gas, i.e. sour gas. Indeed, the combined effect of flammability and toxicity of such gases has the critical potential to increase the hazard level in the industrial installation, thus aggravating the consequences for human and assets. In this work, a detailed kinetic model was validated and adopted to estimate the laminar burning velocity and the flammability limits of sour gas at different initial temperatures, within the range 250–325 K, equivalence ratio from 0.4 to 2.5, and content of H2 S up to 15%v/v with respect to methane. For larger amount of the acid, almost negligible variations of the burning velocity of the mixtures have been observed, even if slight variations are detected either at lean (decrease) or rich (increase) conditions. On the contrary, flammability limits results show also that the addition of H2 S has a strong relevance on safety parameters, more specifically for the upper flammability limit.